Basic study on path planning method utilizing iterative reversing maneuvers at narrow L-junctions - Ryuzo HAYASHI; Koki TAHIRA (Mechanical Engineering Journal)
The purpose of this paper is to discuss a path planning method for navigating narrow L-junctions using iterative reversing maneuvers, as one of the technologies necessary for achieving full self-driving system. First, an analysis of the vehicle's behavior during repeated reversing maneuvers is conducted. Next, based on the analyzed characteristics, a strategy for navigating narrow L-junctions using reversing maneuvers is discussed. Following the proposed strategy, the necessary turning trajectories—constituting segments of the overall path—are formulated sequentially, and the complete path is derived geometrically. Furthermore, an algorithm for generating the entire path from the entrance to the exit is proposed by utilizing the formulated trajectories. The proposed algorithm is validated through numerical simulations. Path generation is performed under varying road width conditions, and it is confirmed that the paths are generated as intended. Additionally, path generation is conducted under a comprehensive range of road width conditions, and it is verified whether the path generation is successful or deemed infeasible. As a result, it is confirmed that the path generation method utilizing reversing maneuvers allows for a wider range of road width conditions to be successfully navigated compared to when reversing maneuvers are not used, indicating the effectiveness of the proposed method. However, after checking for interference with the road boundaries for all path generation results, it is found that in some conditions, the generated paths interfered with the road boundaries, indicating the need for further improvement.